2008
DOI: 10.4049/jimmunol.181.8.5551
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Human Respiratory Virus-Specific CD8+ T Cell Responses in Blood and Airways during Episodes of Common Cold

Abstract: We determined the dynamics of CD8+ T cells specific for influenza virus and respiratory syncytial virus in blood and tracheostoma aspirates of children during the course of respiratory infections. We showed that during localized respiratory infections the ratio of activated effector CD8+ T cells to resting memory/naive CD8+ T cells in peripheral blood increased significantly. Furthermore, the number of effector/memory T cells specific for respiratory viruses declined in blood and increased in the airways, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 26 publications
2
50
1
Order By: Relevance
“…However, the frequency of RSV-specific CD8 T cells in the BAL increased during convalescence suggesting that these cells formed a memory CD8 T-cell population. Additional work by the same group also revealed similar results from tracheal aspirate samples [44]. The RSV-specific CD8 T-cell response remained low comprising less than 2% of total CD8 T cells for the epitope assessed.…”
Section: • • General Kineticssupporting
confidence: 73%
See 1 more Smart Citation
“…However, the frequency of RSV-specific CD8 T cells in the BAL increased during convalescence suggesting that these cells formed a memory CD8 T-cell population. Additional work by the same group also revealed similar results from tracheal aspirate samples [44]. The RSV-specific CD8 T-cell response remained low comprising less than 2% of total CD8 T cells for the epitope assessed.…”
Section: • • General Kineticssupporting
confidence: 73%
“…CD8 T cells from C57BL/6 mice primarily recognize the immunodominant M 187-195 epitope. Although numerous CD8 T-cell epitopes have been identified in humans, in contrast to mice, the frequency of responding cells that can be detected in the airways is typically very low (<2%) [43,44]. F 551-559 IAVGLLLYC A2 C12 [58] M 195-203 IPYSGLLLV A2 B51 [46] M 229-237 YLEKESIYY A2 A1 [46] M2 64-72 AELDRTEEY A2 B44 [46] M2 151-159 RLPADVLKK A2 A3 [46] N 255-263 QVMLRWGVL A2 B8 [57] NS2 41 Additional human CD8 T-cell epitopes against RSV have been identified using computational prediction and MHC binding assays, but require further confirmation [59].…”
Section: • • Cd8 T-cell Epitopesmentioning
confidence: 99%
“…1 T cells in infants and an association with viral clearance and/or recovery (19,21,31). However, by integrating our results on airway T cell content from multiple VRTI with disease severity and ALI, we reveal an association of the persistence of airway CD8 1 T cells with ALI and disease progression.…”
Section: Discussionmentioning
confidence: 88%
“…The overall functional capacities of human infant T cells as being skewed toward Th2 or antiinflammatory responses (8) is largely derived from studies of umbilical cord blood (24)(25)(26). Measuring the in vivo infant immune response to VRTI has been more challenging, and has involved characterization of cells and cytokines in peripheral blood (6,21,27,28), nasopharyngeal washes (29,30), or tracheal aspirates (31,32). However, sampling remains limited, and unifying immune parameters related to disease outcome and severity has not emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Once the virus infection is cleared, the CTL response contracts rapidly, but memory T cells persist, which can be recalled upon a subsequent infection with influenza A virus (8). The rapid decrease of virus-specific CD8 ϩ T cells from the blood may reflect migration of these cells to the site of infection (12). It has been reported that the frequency of Tm ϩ CD8 ϩ T cell is low after 2009 H1N1 influenza virus infection (6).…”
mentioning
confidence: 99%